2005
DOI: 10.1007/s10194-005-0192-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders and pain location in unilateral migraineurs

Abstract: To explore the relationship between the side of pain during attacks and psychopathological features in strictly unilateral migraine, we recruited 35 patients affected by migraine with and/or without aura diagnosed according to the revised ICHD-II criteria. Seventeen patients had right side-locked pain (R-SUM), 11 had left side-locked (L-SUM) and 7 had side-shifting pain (SSM). Patients were administered the Hamilton Anxiety Scale, the State and Trait Anxiety Inventory-State Anxiety, the Beck Depression Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The finding of higher impairment of patients with left-sided symptoms is in line with the literature that shows a slight left-sided preponderance (55–60%) in somatoform disorders ( 38 ) and in somatoform pain ( 39 ). With respect to headaches, a relatively small study suggests that left-sided migraine is more frequently associated with psychiatric symptoms than right-sided migraine ( 40 ). Thus, among tinnitus patients with left-sided headaches, there might be a higher proportion of patients with a somatoform disorder, which can explain the higher impairment in this group.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of higher impairment of patients with left-sided symptoms is in line with the literature that shows a slight left-sided preponderance (55–60%) in somatoform disorders ( 38 ) and in somatoform pain ( 39 ). With respect to headaches, a relatively small study suggests that left-sided migraine is more frequently associated with psychiatric symptoms than right-sided migraine ( 40 ). Thus, among tinnitus patients with left-sided headaches, there might be a higher proportion of patients with a somatoform disorder, which can explain the higher impairment in this group.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation is the lack of a standardised interview to rule out psychiatric conditions in order to perform a correlation with the TCI domains. It is possible that harm avoidance could be related with depression and anxiety disorders, especially in PWM, where the comorbidity with psychiatric conditions is high [52][53][54][55][56][57][58][59]. Also, the lack of a standardised interview avoids a potential comparison between some groups of interest such as patients with aura, where the prevalence of psychiatric conditions is reportedly higher [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Some painful conditions also may have a direct biological relationship with the mental disorders with which they are comorbid. For example, some authors have demonstrated an association between left unilateral migraine and more severe anxiety (and depressive) disorder, implying a possible direct vascular origin for the anxiety [ 29 ].…”
Section: Roots Of Comorbiditymentioning
confidence: 99%